Numerical Response and Density-Dependent Relationship of Menochilus sexmaculatus against Aphis gossypii - F. X. Wagiman (Universitas Gadjah Mada, 1996)
The leaf aphid Aphis gossypii Glover is an important vector of virus disease CVMV (Chilli veinal mottle virus) on chillies. In Malaysia the disease could cause the yield loss up to 60% and the predaceous coccinellid Menochilus sexmaculatus Fabricius was observed a dominant predator in the chilli's ecosystem. The studies had revealed that the coccinellid exhibited a strong numerical response to its prey, A.gossypii. The predator population Y in log(Y-1)) was determined strongly by the aphid population X in log(X+ 1). The immediate numerical response model was Y = -0,1148 + 0.3046X with r^2 = 0.81 and P<0.001, while the 3-day delayed numerical response model was Y = -0,1076 + 0.2962X with r^2= 0.75 and P<0.001. The coccinellid showed its power to stabilise A. gossypii population as indicated by the anti-clockwise direction of cyclic form of their delayed density-dependent relationship.",